Big Insights From a Small Country: The Added Value of Integrated Assessment in the Marine Environmental Status Evaluation of Malta - Borja, Angel; Menchaca, Iratxe; Garmendia, Joxe Mikel; Franco, Javier; Larreta, Joana; Sagarminaga, Yolanda; Schembri, Yasmin; González, Rocío; Antón, Rocío; Micallef, Tamara; Camilleri, Sarah; Solaun, Oihana; et al. (Frontiers in Marine Science, 2021)
In the last few years, the concept of ecosystem-based approach has led to the need for developing integrative assessments that consider the different ecosystem components all together. In Europe, the Marine Strategy Framework Directive (MSFD) aims at achieving the Good Environmental Status for all regional seas. This requires Member States (MS) to implement monitoring networks and assess the status in six-years management cycles, based on 11 qualitative descriptors, ranging from biodiversity to noise. For that assessment MS must apply criteria and methodological standards, following certain specifications. However, the number of MS which have undertaken quantitative assessments, or aggregated the different criteria and/or descriptors in holistic assessments, remains low. This is probably due to the few available tools that enable the aggregation of information at different scales (spatial, temporal) and the integration of a diverse range of indicators. In order to identify the main constraints tied to the integration of data from different indicators, criteria and descriptors, this study involved a comparative analysis of a national assessment of official marine data reported by Malta with the integrative Nested Environmental status Assessment Tool (NEAT). In total, we have used 282 indicators, 24 criteria, 7 descriptors, and 12 ecosystem components. The results showed a good agreement in the assessment at the indicator level (as applied in the national assessment) and threw light on the advantages of integrating the information at criteria, descriptor or ecosystem component levels, when using NEAT. Such integration allows for a global assessment of status of Malta’s marine waters whilst allowing for the identification of management measures at different spatial levels and for different ecosystem components. Lessons learnt from this case study are applicable to remaining assessments for other European MS.